2020
DOI: 10.22159/ajpcr.2020.v13i11.39354
|View full text |Cite
|
Sign up to set email alerts
|

Boswellia Serrata Roxb. – A Bioactive Herbs With Various Pharmacological Activities

Abstract: Herbal medicine has become a medicinal as well as the economic aspect of global significance. While the use of these herbal medicines has increased, there are several questions about their consistency, protection, and effectiveness in different countries. Boswellic acid (BA) is one of the active constituents obtained from plant Boswellia serrata (BS) family Burseraceae. The oleoresin gum of the plant is also known as Salai guggul, Indian olibanum, or Indian frankincense. Boswellia species comprises a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Experimental and clinical studies have suggested the beneficial effects of herbal medicine in neurodegenerative conditions. Previous studies have indicated that plant-derived terpenoids positively affect neurodegeneration . BAs are triterpenoid and hydrophobic compounds extracted from the resin of Boswellia plant species and they possess anti-inflammatory, antioxidant, and antiedema properties. It has been shown that BA can ameliorate memory deficit in animal AD models . However, their mechanism of action is not clearly understood. , Previous studies showed BA possesses therapeutic potential in the tau protein and in microtubule stability, including in Alzheimer’s disease. , The therapeutic application of BA has been limited because of its low aqueous solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies have suggested the beneficial effects of herbal medicine in neurodegenerative conditions. Previous studies have indicated that plant-derived terpenoids positively affect neurodegeneration . BAs are triterpenoid and hydrophobic compounds extracted from the resin of Boswellia plant species and they possess anti-inflammatory, antioxidant, and antiedema properties. It has been shown that BA can ameliorate memory deficit in animal AD models . However, their mechanism of action is not clearly understood. , Previous studies showed BA possesses therapeutic potential in the tau protein and in microtubule stability, including in Alzheimer’s disease. , The therapeutic application of BA has been limited because of its low aqueous solubility and bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…After the bacterial incubation period, two previously selected teeth were dissected longitudinally with a disc to the third middle section of the root. Teeth were transferred into the laminar flow hood to continue dissection using a metal spatula [12]. Teeth sections were dehydrated in an acetone solution series (50%–100%) and then imaged by Carl Zeiss scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1. The extraction techniques and operating conditions for active ingredients from frankincense resin [13] In the last two decades, extracts of resin obtained from the tree of B. serrata have become increasingly popular in the Western world [6]. Standardized preparations of Indian frankincense extracts are commercially available and used to treat inflammatory diseases [14].…”
Section: Extracts Of Resinmentioning
confidence: 99%